PERKEMBANGAN PONDOK PESANTREN RIYADLUL ULUM WADDA'WAH CONDONG KOTA TASIKMALAYA TAHUN (1986-2019) - Anggi Ginanjar, - (2020)
This thesis is entitled "Development of Riyadlul Ulum Wadda'wah Condong Islamic Boarding Schools Tasikmalaya City Year (1986-2019)". The author is interested in studying about Riyadlul Ulum Wadda'wah Condong Islamic Boarding Schools because this boarding school is able to survive in the midst of the times. Since its founding in 1864, the boarding school Riyadlul Ulum Wadda'wah Condong growing and progressing from year to year. Progress seen boarding facility when built starting formal education in boarding schools and modernize the education program. The main problems that will be discussed in this thesis are development of Riyadlul Ulum Wadda'wah Condong Islamic Boarding Schools Tasikmalaya City Year (1986-2019). The main problem is divided into four research questions 1) how backgrounds establishment Riyadlul Ulum Wadda'wah Condong Islamic boarding school in Tasikmalaya City Year (1986-2019)? 2) how is the picture of life in the Riyadlul Ulum Wadda'wah Condong Islamic boarding school in Kel. Setianegara Kec. Cibeureum, Tasikmalaya City, 1986-2019? 3) how the community views the existence of the Riyadlul Ulum Wadda'wah Condong Islamic boarding school in Kel. Setianegara Kec. Cibeureum, Tasikmalaya City? 4) How is the influence of the Riyadlul Ulum Wadda'wah Condong Islamic boarding school on the surrounding environment. This research use historical methods. The steps taken is heuristic, criticism, interpretation, and writing (historiography). collection and research resources, in addition to using literature study, the authors also interviewed perpetrators and witnesses sources of history. The findings of this study indicate that its establishment Riyadlul Ulum Wadda'wah Condong Islamic boarding school motivated by the needs of the community and the initiative of K.H. Nawawi with a 400 tumbak land wakap from Prince Kornel Sumedang. The purpose of establishing the establishment Riyadlul Ulum Wadda'wah Condong Islamic boarding school is to build plenary human beings who have good morals, have scientific insight and are competitive in facing the era of globalization which is based on amaliyah science, scientific charity and the motto of living once a life is meaningful. n the period 1986-2019 there was rapid development at the Riyadlul Ulum Wadda'wah Condong Islamic boarding school. This can be seen with the addition of facilities and infrastructure for the pesantren, the construction of formal schools in the pesantren environment, and the number of students who come to increase every year. The development of Riyadlul Ulum Wadda'wah Condong Islamic boarding school does not only occur in the facilities but also in education, building, social and economic programs. The Riyadlul Ulum Wadda'wah Condong Islamic Boarding School has modernized its curriculum by adding a new curriculum, namely Gontor and the national curriculum in addition to teaching classical or salafi books. The public's view of the existence of the Riyadlul Ulum Wadda'wah Condong Islamic Boarding School is a reference in resolving problems, especially those related to religious law. The Riyadlul Ulum Wadda'wah Condong Islamic Boarding School also has a positive influence on society in terms of education, economy and socio-culture. Keywords: Islamic boarding school, salafi, Riyadlul Ulum Wadda'wah Condong